2020
DOI: 10.13171/mjc02004161378ahy
|View full text |Cite
|
Sign up to set email alerts
|

Rotational barrier and electron-withdrawing substituent effects: Theoretical study of -conjugation in para-substituted anilines

Abstract: The rotational barrier RB around C–NH2 bond between the minimum and maximum states of 84 electron-withdrawing groups at para-position in aniline were studied at the density functional wB97X-D/6-31G** level. The rotational barrier was found to correlate strongly with shortening of the C–NH2 bond, increase of flattening of NH2 group, decrease in negative natural charge on amino nitrogen, increase in minimum ionization potential around lone pair of amino nitrogen, increase in maximum (positive) electrosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…Models other than EDF2/6-31G* in Spartan'14 are not accurately corrected for chemical shifts and they show inconsistency in the relative positions of NMR peaks. The approach using ωB97X-D/6-31G** was used in the current work as it is a preferred computational model for such studies on parasubstituted anilines [14] and disubstituted 1,3-butadienes. [20] Energies of the minimum and transition states in both theoretical methods were corrected for zero-point energies from the measurement of IR vibrational frequencies except in calculation of stabilization energy where they almost cancel out in [Eq.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Models other than EDF2/6-31G* in Spartan'14 are not accurately corrected for chemical shifts and they show inconsistency in the relative positions of NMR peaks. The approach using ωB97X-D/6-31G** was used in the current work as it is a preferred computational model for such studies on parasubstituted anilines [14] and disubstituted 1,3-butadienes. [20] Energies of the minimum and transition states in both theoretical methods were corrected for zero-point energies from the measurement of IR vibrational frequencies except in calculation of stabilization energy where they almost cancel out in [Eq.…”
Section: Methodsmentioning
confidence: 99%
“…The relatively smaller change in the above mentioned parameters in transition states is because the conjugation is the lowest in these states [14] and therefore changing substituents has a smaller effect on their values. Data of the strong electron-accepting CN and NO2 substituents show opposite trends in comparison to all other electron-donating substituents as shown in Tables 1-3.…”
Section: Doi: 105562/cca3672mentioning
confidence: 99%
See 2 more Smart Citations
“…Some geometric, atomic, and molecular parameters have been calculated in this study to investigate further the governing reason behind the trend of BDE/BDEt with the nature of the substituent. Previous studies have reported that RB is a valid and valuable measure for the stability in para-substituted anilines [35], parasubstituted benzaldehydes [36], as well as in disubstituted 1,3-butadienes [37] through resonance or inductive effects. Hence, the correlation of the BDEs/BDEts of 27 para-substituted anilines and phenols with RB is a particular focus of interest in the current work.…”
Section: ■ Introductionmentioning
confidence: 99%